A history of the animal world in the ancient Near East - Collins, Billie Jean (Handbuch der Orientalistik. Nahe und der Mittlere Osten, 2002)
This title concerns man's contact with the animal world: sacrifice, sacred animals, diet, and domestication. Chapters on art, literature, religion and animal husbandry reveal a picture of the complex relationships between the peoples of the Ancient Near East and (their) animals.